DOI: 10.14264/fa9c8be
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Transition in Papua New Guinea (PNG): An Assessment of the Nutrition Transition for Three Diverse Populations, Including the Contributing Factors, Food Insecurity, and Health Risks

Abstract: Background Nutrition transition refers to changes in diets and physical activity patterns as countries undergo economic growth, urbanisation with increased reliance on the global food supply. It is associated with a rapid increase in obesity and diet-related non-communicable diseases (NCDs). Although NCDs are increasing worldwide, the rise in low-and middle-income countries (LMICs) has become more rapid, with greater implications because of the double burden of diseases with the concurrent burden of infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 159 publications
(485 reference statements)
0
1
0
Order By: Relevance
“…While the PNG government's 2021-2030 National Health Plan recognises nutrition as a determinant of health and includes nutrition in their KRAs [2], there is a scarcity of contemporary dietary intake data amongst the PNG population. Most studies identified in this scoping review were published prior to the year 2000 and, therefore, are not reflective of the current food environment or the recent dietary changes, particularly in urban areas experiencing the nutrition transition [62]. It is important to understand the social and cultural contextualisation of dietary behaviours in PNG.…”
Section: Discussionmentioning
confidence: 99%
“…While the PNG government's 2021-2030 National Health Plan recognises nutrition as a determinant of health and includes nutrition in their KRAs [2], there is a scarcity of contemporary dietary intake data amongst the PNG population. Most studies identified in this scoping review were published prior to the year 2000 and, therefore, are not reflective of the current food environment or the recent dietary changes, particularly in urban areas experiencing the nutrition transition [62]. It is important to understand the social and cultural contextualisation of dietary behaviours in PNG.…”
Section: Discussionmentioning
confidence: 99%
“…As with other Low to Middle-Income Countries (LMIC) across the Pacific, PNG is undergoing rapid economic growth, social transition and urbanisation due to increasing resource development [4]. This has coincided with the nutrition transition phenomenon whereby the population's traditional diet and physical activity behaviours have shifted to more processed, high-energy dense foods, increased dependence on global food supply and sedentary activity [4].…”
Section: Introductionmentioning
confidence: 99%
“…As with other Low to Middle-Income Countries (LMIC) across the Pacific, PNG is undergoing rapid economic growth, social transition and urbanisation due to increasing resource development [4]. This has coincided with the nutrition transition phenomenon whereby the population's traditional diet and physical activity behaviours have shifted to more processed, high-energy dense foods, increased dependence on global food supply and sedentary activity [4]. Similar to other Pacific LMICs, where the economic and nutrition transition have been associated with increased NCD prevalence [5,6], in PNG, the nutrition transition is more apparent in regions with higher exposure to urbanisation and modernisation and therefore, the peri-urban and urban populations are at higher risk of NCDs such as CVD and T2DM compared to their rural counterparts [7,8].…”
Section: Introductionmentioning
confidence: 99%